"Stuff From Back Home": Enda Walsh's The Walworth Farce - Eamonn Jordan (Ilha do Desterro)
Since its first performance in 2006 by Druid Theatre Company, Enda Walsh's award-winning The Walworth Farce has toured Ireland, Britain, America, Canada, New Zealand and Australia to great acclaim, with the brilliance of the directing, design and acting engaging with the intelligence and theatricality of Walsh's script. The play deals with a family, who as part of a daily enforced ritual, re-enact a farce, written and directed by Dinny, the patriarch, a story which accounts for their exile in London, and away from their family home in Cork. Their enactment is an attempt to create a false memory, for their performance is very much at odds with the real events which provoked their exile.